Non‐contact vital signs monitoring in broiler chickens - Md. Shafkat Hossain; Sourav Kumar Pramanik; Atikur Rahman; Shahin Ali; Shekh Md Mahmudul Islam (The Journal of Engineering, 2023)
Abstract Measuring the heartbeat and respiration of animals continuously can provide valuable information about their health status. Respiratory‐related diseases are very common in the poultry industry and unfortunately, there is no non‐contact respiratory monitoring system for measuring the breathing rate and heart rate of the broiler chicken. In this letter, the authors explored and tested the feasibility of utilizing a 24‐GHz continuous‐wave (CW) radar module for monitoring the vital signs (breathing rate and heart rate) of broiler chickens. A signal processing approach has been developed to extract vital signs of broiler chicken from Radar‐captured signals. The experiment was carried out on three different normal broiler chickens with the ages of 25–30 days, weight 1.18–1.6 kg where a 24‐GHz radar module was mounted at a distance of 0.2 m above the chest surface of the chicken, and this particular experiment was repeated for 20 times. The authors also used a reference ECG module (Biopac System) for extracting the breathing rate and heart rate of the broiler chicken and compared the accuracy of their proposed system. Experimental results demonstrated that the radar measurement closely matches the Biopac ECG acquisition module measurement and showed an accuracy of 96% for a short‐scale study.